Endodontic Surgery of a Symptomatic Overfilled MTA Apical Plug: A Histological and Clinical Case Report - Asgary, Saeed; Fayazi, Sara (Iranian Endodontic Journal, 2017)
This case report presents the successful surgical treatment of a symptomatic open apex upper central incisor with a failed overfilled mineral trioxide aggregate (MTA) apical plug. Unintentional overextension of the MTA had occurred two years before the initial visit. An apical lesion adjacent to the excess MTA was radiographically detectable. Endodontic surgery was performed using calcium-enriched mixture (CEM) cement as a root-end filling material. Curettage of the apical lesion showed a mass of unset MTA particles; histopathological examination revealed fragments of MTA and granulation tissues. Up to 18-month follow-up, the tooth was clinically asymptomatic and fully functional. Periapical radiograph and CBCT images showed a normal periodontal ligament around the root. In conclusion, favorable outcomes in this case study suggested that root-end filling with CEM cement might be an appropriate approach; in addition, however many factors probably related to the initial failure of the case, the extrusion of MTA into the periapical area should be avoided. Keywords: Apical barrier; Apicoectomy; Calcium-Enriched Mixture; CEM Cement; Endodontics; MTA; Surgical treatment